The Long-Term Performance of Corporate Bonds (And Stocks) Following Seasoned Equity Offerings - Eberhart, Allan C.; Siddique, Akhtar (Review of Financial Studies, 2002)
Previous studies document negative long-term abnormal stock returns following seasoned equity offering (SEO) issuances and conclude that markets are inefficient. Other studies, however, argue that these results are a manifestation of risk mismeasurement (i.e., the bad-model problem), not market inefficiency. We test the efficient market hypothesis (EMH) and avoid the bad-model problem by examining the long-term performance of our sample firms' bonds and stocks following their SEOs. Our results are inconsistent with the EMH. We also provide evidence that SEOs transfer wealth from shareholders to bondholders because SEOs reduce default risk.